An attempt of resistivity map convolution - Lapajne, Janez (Geologija, 1980)
An attempt of resistivity data convolution has been made to produce grid residual and approximate second derivative maps. Twodimensional filters, common in filtering of potential field data, have been used as operators. For convolution a smoothed resistivity map has been prepared, and for interpretation only a rough result — zero lines marking out low resistivity and high resistivity sections has been taken into account. These sections correspond to different lithological units, the zero lines, however, to lithological boundaries and faulted zones. A resistivity map of the Čatež thermal springs area made previously is used to illustrate the practical application of the convolution method. The purpose of geoelectrical survey was to determinate lithological relations below shallow Quaternary gravel deposits and to find faulted zones, where thermal water could rise from a deepseated aquifer. The interpretation of these maps and other geophysical data enabled the location of two successful bore holes yielding abundant thermal water. Approximate second derivative resistivity maps prepared subsequently show that the locations of these bore holes lie in a zero line. Although resistivity data are not potential field data, the second derivative resistivity map seems to be quite useful.